The Contribution of Islamic Sciences to Promoting Values of Tolerance and Rejecting Intolerance - Abdullah, Prof. Dr. Raed Amir Abdullah (Sulaimani Journal for Humanities, 2026)
Human values are considered fundamental pillars of civilized societies, with tolerance, rejection of fanaticism, and intellectual openness being among the most essential values that promote understanding and peaceful coexistence. This study highlights the pivotal role of Islamic sciences in fostering these values through their texts and teachings that advocate for compassion, justice, and acceptance of others. The study also examines the historical contributions of Islamic sciences to the development of Islamic civilization and the enrichment of human thought, emphasizing their potential to confront manifestations of extremism and intolerance in the modern era. Furthermore, it offers a scientific and practical vision to enhance intercultural dialogue andhuman coexistence, focusing on how to instill values of tolerance and reject fanaticism through a comprehensive analysis of Islamic intellectual texts.
Keywords: Islamic sciences; tolerance; extremism